RELIABILITY ESTIMATION OF MECHANICAL SEALS BASED ON ARTIFICIAL HUMMINGBIRD ALGORITHM AND THREE⁃PARAMETER WEIBULL DISTRIBUTION - LI AnHong; ZHU JunHua; YU Ling (Jixie qiangdu)
In order to quickly and accurately evaluate the reliability of mechanical seals,the three⁃parameter Weibull distribution was used to model the mechanical seal failure data.The reliability evaluation problem of mechanical seal was transformed into a constraint optimization problem,and a reliability evaluation method based on artificial hummingbird algorithm(AHA)was proposed.Through numerical simulation and case analysis,maximum likelihood estimation(MLE),improved Harris Hawks optimization(IHHO)algorithm and AHA were used to compare calculation accuracy and operational efficiency in solving the Weibull distribution parameter estimation problems.The results show that the parameter estimation using AHA has advantages of faster convergence speed and higher accuracy,and it can shorten the optimization time and improve the accuracy compared with MLE algorithm and IHHO algorithm,which provides a new and efficient method for Weibull parameter estimation of mechanical seals.